Experiences of cervical screening participation and non‐participation in women from minority ethnic populations in Scotland. (17th June 2021) - Nelson, Mia; Patton, Andrea; Robb, Katie; Weller, David; Sheikh, Aziz; Ragupathy, Kalpana; Morrison, David; Campbell, Christine
Abstract: Background: The introduction of screening in the UK and other high‐income countries led to a significant decrease in the incidence of cervical cancer and increase in survival rates. Minority ethnic groups are often underrepresented in screening participation for reasons that are poorly understood. Objective: To explore experiences of cervical screening participation and non‐participation of women from minority ethnic populations in Scotland and gain insights to support the development of interventions that could potentially support screening participation and thereby reduce inequalities. Design: Qualitative comparison group study using in‐depth, semi‐structured individual interviews that were thematically analysed. Setting and participants: This study took place in Scotland. Fifty women were purposively sampled from four ethnic minority groups: South Asian; East European; Chinese; and Black African or Caribbean. White Scottish women were also interviewed. Results: Many experiences described were common regardless of ethnicity, such as difficulties managing competing priorities, including work and care responsibilities. However, important differences existed across the groups. These included going abroad for more frequent screening, delayed introduction to screening and not accessing primary care services, language difficulties in health‐care settings despite proficiency in English and not being sexually active at screening commencement. Experiences of racism, ignorance and feeling shamed were also reported. Conclusions: Key differences exist in the experience of minority ethnic groups in Scotland. These offer potential opportunities to reduce disparity and support screening participation including maximizing co‐incidental interactions and developing outreach work.